THU0078 Interactions of Antibodies Against Citrullinated Peptides with HLA Shared Epitope, PTPN22 1858T Variant, and Smoking in Individuals Prior to and after the Development of Rheumatoid Arthritis. (23rd January 2014) - Kokkonen, H.; Brink, M.; Hansson, M.; Mathsson, L.; Lassen, E.; Jakobsson, P. J.; Holmdahl, R.; Rönnelid, J.; Klareskog, L.; Rantapää Dahlqvist, S.
Abstract : Background: Presence of antibodies against cyclic citrullinated peptides (ACPA) has been demonstrated to precede the development of rheumatoid arthritis (RA) by several years. The gene-environment interaction for these antibodies has not been clarified. Objectives: To analyse for the development of reactivity against citrullinated peptides in the pre-disease phase of RA and after the onset of disease (i.e. diagnosis) in relation to genetic and environmental factors. Methods: This study comprised 406 individuals, providing 717 samples who were identified before onset of symptoms of RA (median (IQR) 7.4 (9.3) years) as donors to the Medical Biobank of Northern Sweden. Among these, 204 were also sampled at the time of diagnosis. Analyses of antibodies against 10 different citrullinated peptides; Filaggrin, α-enolase (CEP1), collagen citC1 (CitC1 III ), Fibrinogen (Fib) α591, Fibα573, Fibβ72, Fibβ74, Fibβ36-52, Vimentin (Vim) 60-75, and Vim2-17 were performed using the ImmunoCAP ISAC®system (Phadia Diagnostics, Uppsala). Anti-CCP2 antibodies were analysed using ELISA (Euro-Diagnostica). HLA-SE alleles were genotyped using polymerase chain reaction sequence specific primers and genotyping of the PTPN22 1858C/T polymorphism was performed using a Taqman instrument. Results: In individuals prior to onset of symptoms of RA, being positive for HLA-SE was associated with antibodies against Fibβ72, Fibβ74, and CCP2. HLA-SE positivity was associated with the development of antibodies against CCP2, Fibβ36-52, CEP-1, and Vim60-75 in individuals who prior to onset of symptoms were negative for the respective antibody but at the time of diagnosis turned positive. Smoking was associated with the development of positivity for Filaggrin, CEP-1, CitC1 III, Fibα591, Fibα573, Fibβ36-52, and Vim60-75 antibodies. Interaction of smoking and HLA-SE after disease onset further increased the risk for development of antibodies against Filaggrin, Fibβ36-52, and CCP2. Conclusions: Conversion to positivity for several of the antibodies after disease onset was associated with HLA-SE and/or smoking which was less evident during the pre-dating period. The different patterns in associations of the genetic markers and smoking with the various antibodies may reflect differences in the pathways leading to antibody development. Disclosure of Interest: None Declared